Pediatric Motor Stereotypies: An Updated Review - Subki, Ahmed H.; Alsallum, Mohammed S.; Alnefaie, Majed N.; Alkahtani, Abdulaziz M.; Almagamsi, Sameer A.; Alshehri, Zaher S.; Kinsara, Rayyan A.; Jan, Mohammed M. (Journal of Pediatric Neurology, 2017)
Motor stereotypies are repetitive, purposeless movements that cannot be categorized into any of the known pathological movement disorders. They can be “primary,” occurring in normal children as a normal physiological variation or “secondary,” occurring in children with autism, intellectual disability, or other developmental disorders. Observation and videotaping are crucial for excluding seizures and other pathological movement disorders. They usually last for seconds to minutes and can occur spontaneously or be triggered by fatigue, excitement, or stress. Another key feature is the ability to suppress these movements by distraction or sensory stimulation. In this article, we aim to present an updated review of this topic and highlight important diagnostic tips and management pitfalls. Recognition of such movements is critical to prevent unnecessary investigations or treatments.
Keywords: child; motor; stereotypy; review; update